Hinduism in Animal de fondo by Juan Ramón Jimenez - Christine Steffen (Studies in 20th & 21st Century Literature, 1991)
Animal de fondo (1949), by Juan Ramón Jimenez, is an enigmatic and joyous recounting of a mystical trance which the poet experienced during a sea voyage from New York to Buenos Aires in 1948. This essay approaches the poems from the perspective of classic Hindu religious traditions. The conciencia frequently used by Juan Ramón to express integration with the natural world is analogous to Brahman, the all-pervading reality which for the Vedic poets includes everything from the life of man to sticks and stones. The apparent polytheism of Animal de fondo echoes Vedic hymns, which deify many important social and natural elements. The Hindu concept of dharma, the sacred law of society regulating moral order, duties, and forms of conduct appropriate for different classes or persons, appears in poems where the poet exults in his poetizing function. Juan Ramón assimilated elements of the relativist-pluralist Hindu tradition that relegated questions of dogma to secondary importance, and, like the Vedic hymn-makers, was able to capture religious reality that was reflected in his own heart and mind and affirm it joyously.
Keywords: Animal de fondo; Spanish literature; Juan Ramón Jimenez; mysticism; Hinduism; Hindu religious traditions; conciencia; consciousness; natural world; Brahman; Vedic poets; polytheism; dharma; relativism; pluralism; joy